Ability of Infrascanner 2000 to predict post-traumatic cranial hemorrhage volume in low-resource settings: a protocol for a multi-center prospective, observational study. Issue 1 (21st February 2022) - Fernandez, Laura L; Griswold, Dylan P; Aristizabal, Sarita; Sanchez, Diana M; Rubiano, Andres M
Abstract: Low- and middle-income countries experience three times more traumatic brain injury (TBI) cases when compared with their high-income country counterparts. The quality of care patients receive in the prehospital setting and emergency department settings are highly variable and often dependent on computed tomography (CT) availability. The implementation of a handheld device that is able to reliably diagnose intracranial hemorrhage (ICrH) in TBI patients is needed in these settings where CT is unavailable. The Infrascanner has shown promise to detect intracranial bleeds in patients with moderate TBI. We aim to determine the correlation between the coefficient provided by the Infrascanner compared to the post-traumatic supratentorial hemorrhagic collections volume in patients with surgical indication in differente trauma centers. This is a multi-center prospective observational study that will be carried out in three trauma centers in Colombia, Guatemala and Pakistan. We calculated a sample size of eighty-six patients with mild, moderate or severe TBI ≥ 15 years old who have a supratentorial hemorrhage abnormality that requires neurosurgical intervention. The Infrascanner's ability to detect IChR in patients with surgical indications associated to hemorrhage volume when compared with CT is the primary outcome measure. Secondary outcome measure is the correlation of the mean of the six Infrascanner measurement values compared with volume of ICrH as measured from the six manual head CT segmentation measurements. ICrH volume correlation and agreement will be evaluated by the Pearson coefficient and Bland-Altman analysis, and a linear regression analysis will be performed in order to predict IChR from the Infrascanner measurement.